Prevalence and associated factors of structural congenital anomalies in resource limited setting, 2023: a systematic review and meta-analysis - Geda, Yohannes Fikadu; Lamiso, Yirgalem Yosef; Berhe, Tamirat Melis; Chibsa, Samuel Ejeta; Sahle, Tadesse; Assefa, Kenzudin; Mohammed, Seid Jemal; Abeje, Seblework; Gesese, Molalegn Mesele (Frontiers in Pediatrics, 2023)
Background: Several studies have been conducted on structural congenital anomalies. However, there is a paucity of studies with a comprehensive review of structural anomalies. We aimed to verify the available articles to pool possible risk factors of structural congenital anomalies in resource limited settings.Setting: Genuine search of the research articles was done via PubMed, Scopus, Cochrane library, the Web of Science; free Google database search engines, Google Scholar, and Science Direct databases. Published studies were searched and screened for inclusion in the final analysis, and Studies without sound methodologies, and review and meta-analysis were not included in this analysis.Participants: This review analyzed data from 95,755 women who gave birth as reported by primary studies. Ten articles were included in this systematic review and meta-analysis. Articles that had incomplete information and case reports were excluded from the study.The overall pooled effect estimate of structural congenital anomalies was 5.50 [4.88-6.12] per 100 births. In this systematic review and meta-analysis maternal illness effect estimate (EI) with odds ratio (OR) =4.93 (95%CI 1.02-8.85), unidentified drug use OR =2.83 (95%CI 1.19-4.46), birth weight OR =4.20 (95%CI 2.12-6.28), chewing chat OR =3.73 (95%CI 1.20-6.30), chemical exposure OR =4.27 (95%CI 1.19-8.44) and taking folic acid tablet during pregnancy OR =6.01 (95%CI 2.87-14.89) were statistically significant in this meta-regression.The overall pooled effect estimate of structural congenital anomalies in a resource limited setting was high compared to better resource countries. On the Meta-regression maternal illness, unidentified drug use, birth weight, chewing chat, chemical exposure and never using folic acid were found to be statistically significant variables. Preconception care and adequate intake of folic acid before and during early pregnancy should be advised.